2012
DOI: 10.2174/156802612799078720
|View full text |Cite
|
Sign up to set email alerts
|

Translocator Protein as a Promising Target for Novel Anxiolytics

Abstract: Neurosteroids are able to rapidly control the excitability of the central nervous system, acting as regulators of type A receptors for GABA. Over the last two decades, many authors have confirmed that neurosteroid level alterations occur in psychiatric disorders, including anxiety disorders. More recently, investigators have manipulated neurosteroidogenesis in an effort to correct neuronal excitation and inhibition imbalances, which may lie at the root of neuropsychiatric conditions. In line with this strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 130 publications
(215 reference statements)
0
23
0
1
Order By: Relevance
“…The TSPO, which is located mainly in the outer mitochondrial membrane (OMM) in peripheral tissues and the central nervous system (CNS), processes the availability of neurosteroids in the brain by modulating cholesterol [15]. Several studies have shown that TSPO ligands effectively treated depression and anxiety disorders through the modulation of the neurosteroid synthesis [16], [17]. Midazolam, a ligand for TSPO and CBR, has also induced anxiolytic-like and antidepressant effects [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…The TSPO, which is located mainly in the outer mitochondrial membrane (OMM) in peripheral tissues and the central nervous system (CNS), processes the availability of neurosteroids in the brain by modulating cholesterol [15]. Several studies have shown that TSPO ligands effectively treated depression and anxiety disorders through the modulation of the neurosteroid synthesis [16], [17]. Midazolam, a ligand for TSPO and CBR, has also induced anxiolytic-like and antidepressant effects [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Extending our work on gonadal and adrenal steroidogenesis, we demonstrated that brain neurosteroid synthesis was under the control of TSPO drug ligands and endogenous DBI [39], suggesting TSPO ligands may serve as pharmacological means to regulate neurosteroidogenesis [40]. Changes in neurosteroid levels are associated with a variety of psychopathological conditions [41] and induction of neurosteroid formation by TSPO ligands has been a vibrant field of research [40], though the precise cells responsible for synthesis of neurosteroids and TSPO ligand site of action remains to be elucidated.…”
Section: Dbi Tspo Tspo Ligands and Insights Into Steroidogenesismentioning
confidence: 69%
“…In the 3xTgAD mouse model of Alzheimer's disease, TSPO activation was shown to enhance steroidogenesis and neuroprotection (70). Moreover, activation of TSPO has been shown to have anxiolytic actions potentially due to an increase in synthesis of neurosteroids with sedative properties (64, 71, 72). Patients with posttraumatic stress disorder have lower levels of TSPO, and stimulation of TSPO improved behavioral deficits in a mouse model of posttraumatic stress disorder (7375).…”
Section: Discussionmentioning
confidence: 99%